anonymous
  • anonymous
3x + 2y = 6 4x + y = 1 Solve the system of equations
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
from equation 2: y = 1 - 4x
anonymous
  • anonymous
substitute y= 1- 4x in equation 1: 3x + 2(1-4x) = 6
anonymous
  • anonymous
simplifying will give us 3x + 2 -8x = 6 -5x = 4 x = -4/5 = -0.8

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
now substitute x = -4/5 either to equation 1 or 2: then you will get the value of y
zzr0ck3r
  • zzr0ck3r
There is another way, and I think it is often easier \(3x+2y=6\\4x+y=1\) Multiply the second equation by \(-2\) and we get \(3x+2y=6\\-8x+-2y=-2\). Now add the two equations together. \(-5x=4\implies x=-\frac{4}{5}\) Now plug this into anything with an \(x\) and \(y\) to solve for \(y\).

Looking for something else?

Not the answer you are looking for? Search for more explanations.